World Economies and the Distribution of International Branch Campuses - Zhang, Li; Kinser, Kevin; Shi, Yunyu (International Higher Education, 2014)
The international branch campus (IBC) has become a noticeable mode of internationalization in higher education, and has garnered great attention from the public and the media. Perhaps because the United States, the United Kingdom and Australia have been the dominant exporting countries, this phenomenon has sometimes been critiqued as a strategy that promotes the interests of developed countries over those of developing countries. However, our analysis of IBC distribution using an economic framework provided by the World Economic Forum suggests that economic competitiveness is more important to the development of IBCs than a dated developed-to-developing.